Water-based concrete composite anticorrosive paint and preparation method thereof

By using hydrophotic acrylate emulsion and nano -silicon oxide particles made of hydrophone -modified silicon -based silicon -based silicon -based siliconic anticorrosive anticorrosive coatings on the concrete structure, the problem of poor durability failure and poor environmental protection of concrete structure in existing technologies has achieved efficient Anti -corrosion and environmental coating performance.

CN119371866AActive Publication Date: 2025-01-28CHANGAN UNIV

Patent Information

Application Number
CN202411739620.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In the prior art, structures such as road bridges, cement concrete bridge decks, etc. are easily affected by factors such as freeze-thawing, corrosion, alkali aggregate reactions, etc. during service, resulting in the risk of durability failure, and traditional solvent-based anticorrosion coatings have environmental and health. Hidden danger.

Method used

The use of hydrophilic concrete anticorrosive coatings, the preparation method includes the use of hydrophilic organic siliconic acrylate emulsion as a membrane substance, combined with nanoharine particles, to form a dense protective layer through compatibility and cross -linking reactions to improve the corrosion resistance of coating And adhesion.

Benefits of technology

The efficient anti -corrosion of the concrete structure is realized, the pore rate is reduced, the wear resistance and toughness of the coating is enhanced, the life of the coating is extended, and the harm to the environment and human health is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a water-based concrete composite anticorrosive coating and a preparation method thereof, and relates to the field of coatings. A semi-continuous seed emulsion method is adopted, methyl methacrylate, butyl acrylate, acrylic acid and organosilicon monomer gamma-methacryloxypropyltrimethoxysilane (gamma-MPS) are used to obtain a water-based organosilicon modified acrylate emulsion, the water-based organosilicon modified acrylate emulsion is used as a film-forming substance, and then composite hydrophobic modified nano silicon oxide is used as a doped filler to prepare the coating. The water-based concrete composite anticorrosive paint is obtained through a physical blending method. According to the prepared coating, the water-based emulsion is used as a film-forming substance, emission of organic matter is small, the environment-friendly property is high, hydrophobic modified nano-silica is mixed, the reinforcing effect is achieved in the coating structure, the coating has certain toughness due to the cross-linking structure between organic silicon modified acrylate polymers, the hardness and softness combined structure is good, and the coating has the good application prospect. The coating is excellent in mechanical property due to the hydrophobic structure, permeation corrosion of water molecules is avoided, and the coating has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a water-based concrete anticorrosive coating and a preparation method thereof. Background Art

[0002] my country's existing highway bridges, cement concrete bridge decks, guardrails and other structures are often affected by freeze-thaw, corrosion, alkali-aggregate reaction, steel corrosion, mechanical damage and other factors during their service. Concrete structures often peel off in layers, sand and gravel leak out, loose and exposed reinforcement, and will produce epidermal sloughing under the action of stress corrosion. In severe cases, they will swell and loosen. Even if some concrete structures do not have obvious corrosion and deterioration in appearance, their strength is significantly reduced and they are severely damaged. In highway networks and urban construction, a large number of bridge concrete components are not properly maintained on a daily basis, and the bridges are at serious risk of durability failure.

[0003] Various methods have been studied in the past few decades to provide durable concrete and solve the corrosion problem. Before the corrosion damage of concrete components occurs, the method of covering the concrete surface with paint to form a protective coating is one of the most effective and economical methods to reduce the corrosion damage of concrete. The coating can prevent corrosive substances from eroding the substrate, enhance the corrosion resistance of concrete, and improve durability. After the corrosion damage occurs, in addition to taking conventional repair and reinforcement measures, coating protection treatment can still be used.

[0004] The production of traditional solvent-based anti-corrosion coatings uses a lot of organic solvents. The evaporation of solvents during construction not only harms the environment but also affects human health. Therefore, water-based anti-corrosion coatings are low-toxic and harmless, and have become a hot topic of research. Summary of the invention

[0005] The purpose of the present invention is to provide a water-based concrete anticorrosive coating and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a water-based concrete anti-corrosion coating, characterized in that it comprises the following preparation steps:

[0007] (1) providing an emulsifier solution;

[0008] (2) weighing methyl methacrylate, butyl acrylate, acrylic acid, and silicone monomer γ-methacryloxypropyltrimethoxysilane in proportion, mixing them evenly, taking a portion of the mixture as a seed monomer, and adding it dropwise to the emulsifier solution obtained in step (1) to obtain a milky white seed emulsion;

[0009] (3) weighing a pH buffer into a container, adding the white emulsion obtained in step (2) under heating conditions, and reacting until the solution changes from white to blue;

[0010] (4) adding the remaining part of the mixture of step (2) and an initiator, heating, and obtaining an aqueous silicone-modified acrylate emulsion;

[0011] (5) weighing nano-silica, deionized water, anhydrous ethanol, ammonia water, silane coupling agent KH-560, and tetraethyl orthosilicate in proportion in a container, heating and mixing, and then adding a hydrophobic long-chain modifier to react to obtain a modified nano-silica gel;

[0012] (6) washing, drying, and grinding the modified nano-silica gel obtained in step (5) to obtain hydrophobic modified nano-silica particles;

[0013] (7) Adding organosilicon-modified acrylic emulsion to the container, stirring, adding dispersant, wetting agent, hydrophobically modified silicon oxide nanoparticles, stirring evenly, adding film-forming aid, thickener, leveling agent, pH regulator, mildew inhibitor according to proportion, continuing to disperse evenly, and obtaining water-based concrete composite anticorrosive coating. Furthermore, the emulsifier in step (1) is 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, and its mass ratio is 1-3% of the total mass of the four monomers in step (2).

[0014] Furthermore, in step (2), the ratio of methyl methacrylate, butyl acrylate, acrylic acid, and silicone monomer γ-methacryloxypropyltrimethoxysilane is 8-12:10.5-12.5:1:1; and the ratio of the seed monomer is 5% to 15% of the total monomer mass.

[0015] Furthermore, the pH buffer in step (3) is sodium bicarbonate; the initiator in step (4) is ammonium persulfate, and its mass ratio is 0.3-1% of the total mass of the four monomers in step (2); and the hydrophobic long-chain modifier in step (5) is octadecylamine.

[0016] Furthermore, in step (5), the nano silicon oxide has a particle size of 5 to 15 nm and a specific surface area of ​​180 to 220 m 2 / g.

[0017] Furthermore, the dispersant in step (7) is 5040; the leveling agent is RM2020; the thickener is one or more of sodium polyacrylate and polyurethane alkali swelling thickener; the wetting agent is one or two of CF-10, X-450 and TEGO Dispers755W; the film-forming aid is alcohol ester twelve, and the defoaming agent is one or two of BYK306 and F-2-2; the mildew inhibitor is one or two of benzoate and benzyl carbamate chloride; the pH adjuster is 2-amino-2methyl-1-propanol pH adjuster.

[0018] Furthermore, a water-based concrete composite anti-corrosion coating is provided, characterized in that the water-based concrete composite anti-corrosion coating comprises, by components: 80 to 120 parts of water-based silicone-modified acrylate emulsion, 0.5 to 2.5 parts of hydrophobically modified nano-silicon oxide, 0.5 to 2 parts of dispersant, 0.1 to 1 part of leveling agent, 0.5 to 3 parts of thickener, 0.1 to 0.3 parts each of wetting agent and defoaming agent, 1 to 2 parts of film-forming aid, 0.1 to 0.4 parts of mildewproofing agent, and 0.3 to 0.5 parts of pH adjuster; the coating is prepared by the method.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The present invention uses water-based silicone-modified acrylate emulsion as a film-forming substance. When it is coated on the concrete surface, there is an interaction force between the polymer chains on the surface of the emulsion particles, and the particles are close to fuse to form a film; functional groups such as carboxyl in the acrylate segment can undergo a cross-linking reaction under certain conditions, further improving the strength and density of the film, and the silicone segment will migrate to the surface of the film, making the coating hydrophobic. Due to the hydrophobic modification of the surface of the nano-silicon oxide particles, it has good compatibility with the silicone-modified acrylate polymer in the emulsion. During the drying and film-forming process of the coating, the nano-silicon oxide particles will fill in the pores of the polymer film, reducing the porosity of the coating and effectively blocking the corrosive medium; the silicone-modified acrylate polymer film and the nano-silicon oxide particles in the coating form a relatively dense protective layer, further improving the corrosion resistance of the coating.

[0021] In addition, nano-silicon oxide particles play a reinforcing role in the coating. When the coating is subjected to external forces, the nano-silicon oxide particles can bear part of the stress and improve the hardness and wear resistance of the coating. At the same time, the cross-linked structure between the silicone-modified acrylate polymers also makes the coating have a certain toughness, which can resist external forces to a certain extent without breaking. This combination of rigidity and flexibility allows the coating to adapt to the deformation of the concrete structure during use, and will not easily crack or peel off. Furthermore, the functional groups in the acrylate polymer can chemically bond and physically adsorb with the concrete surface, improve the adhesion of the coating to the concrete substrate, and enable the coating to effectively play a protective role for a long time, avoiding peeling and loss of protective function. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the water-based concrete composite anti-corrosion coating prepared in the following examples are as follows:

[0024] First, the surface of the concrete substrate is cleaned with sandpaper to remove large protruding particles and stains, exposing a fresh and clean concrete surface and cleaning it with a brush to remove surface floating and sinking. Where there are cracks, fill the cracks first and level them with putty; spray the composite coating onto the concrete substrate in a manner of spraying small surfaces first and then large surfaces, and spraying evenly from top to bottom, for a total of 3 coats. Before each spraying, the previous coat of coating needs to be sprayed again after the surface is dry. After three sprayings, ensure that there is no missing coating, sagging, uniform coating spraying, and no accumulation of material at the corners.

[0025] Paint status: visual inspection

[0026] Drying time: JG / T 335-2011

[0027] Thickness: GB / T 13452.2-2008

[0028] Salt water resistance: GB / T 9274-1988

[0029] Adhesion: JT / T 695-2007

[0030] Chloride ion penetration resistance: GB / T 50082-2024

[0031] Mass increase rate: m2 -m 1 / m 1 *100%(m 1 is the initial mass, m 2 is the mass after 50 freeze-thaw cycles)

[0032] Compressive strength: GB / T 50081-2019

[0033] Compressive strength loss rate: P 1 -P 2 / P 1 *100%(P 1 is the initial compressive strength, P 2 is the compressive strength after 50 freeze-thaw cycles)

[0034] Example 1

[0035] (1) Weigh 0.58 parts of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate according to the proportion, add deionized water to dissolve, and stir at 25° C. and 800 r / min to make it completely dissolved to obtain an emulsifier solution with a solid content of 48.7%;

[0036] (2) Weigh 10 parts of methyl methacrylate, 12.2 parts of butyl acrylate, 1 part of acrylic acid, and 1 part of silicone monomer γ-methacryloxypropyltrimethoxysilane according to the proportion, stir evenly, take 10% of the total amount as seed monomer, and add dropwise to the emulsifier solution obtained in step (1), at 25° C., 800 r / min, and after sufficient pre-emulsification, obtain a milky white seed emulsion;

[0037] (3) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0038] (4) Weigh 0.2 parts of sodium bicarbonate into a four-necked round-necked flask, add the milky white seed emulsion obtained in step (2), place the flask in a water bath and add a stirring rod, add the milky white seed emulsion obtained in the previous step into the flask and start stirring at a speed of 350 r / min, set the water bath temperature to 72° C., place a condenser tube, and stir while heating; after the water temperature rises to 72° C., continue to keep warm and stir until the seed emulsion in the flask changes from white to blue;

[0039] (5) adjusting the water bath heating temperature to 75° C., continuing to heat and stir, adding the remaining monomer in step (2) and the ammonium persulfate solution obtained in step (3) into two constant pressure funnels respectively, and then dropping them into the flask. After the titration is complete, raising the water bath temperature to 80° C. and maintaining the speed for continuous stirring for 1 hour. After the reaction is complete, filtering and cooling, obtaining an aqueous silicone-modified acrylate emulsion;

[0040] (6) Weigh 3 parts of nano-silicon oxide, 40 parts of deionized water, 20 parts of anhydrous ethanol, 3 parts of ammonia water, 3 parts of silane coupling agent KH-560, and 3 parts of tetraethyl orthosilicate in proportion, place them in a round-bottom flask and put them in a 50° C. water bath for stirring to make them stir evenly; then increase the temperature to 60° C. and add 1 part of saturated octadecylamine solution at one time, and continue stirring at 60° C. for 8 hours to obtain modified gel nano-silicon oxide;

[0041] (7) washing the modified nano-silica gel obtained in step (6) with anhydrous ethanol, centrifuging, drying at 80° C., and grinding to obtain hydrophobically modified nano-silica particles;

[0042] (8) Add 100 parts of organosilicon-modified acrylate emulsion into a container and stir, add 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 0.5 parts of hydrophobically modified silica nanoparticles, stir evenly, then add 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continue to disperse evenly, and let stand for 2 hours to obtain a water-based concrete composite anti-corrosion coating.

[0043] Example 2

[0044] (1) Weigh 0.58 parts of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate according to the proportion, add deionized water to dissolve, and stir at 25° C. and 800 r / min to make it completely dissolved to obtain an emulsifier solution with a solid content of 48.7%;

[0045] (2) Weigh 10 parts of methyl methacrylate, 12.2 parts of butyl acrylate, 1 part of acrylic acid, and 1 part of silicone monomer γ-methacryloxypropyltrimethoxysilane according to the proportion, stir evenly, take 10% of the total amount as seed monomer, and add dropwise to the emulsifier solution obtained in step (1), at 25° C., 800 r / min, and after sufficient pre-emulsification, obtain a milky white seed emulsion;

[0046] (3) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0047] (4) Weigh 0.2 parts of sodium bicarbonate into a four-necked round-necked flask, add the milky white seed emulsion obtained in step (2), place the flask in a water bath and add a stirring rod, add the milky white seed emulsion obtained in the previous step into the flask and start stirring at a speed of 350 r / min, set the water bath temperature to 72° C., place a condenser tube, and stir while heating; after the water temperature rises to 72° C., continue to keep warm and stir until the seed emulsion in the flask changes from white to blue;

[0048] (5) adjusting the water bath heating temperature to 75° C., continuing to heat and stir, adding the remaining monomer in step (2) and the ammonium persulfate solution obtained in step (3) into two constant pressure funnels respectively, and then dropping them into the flask. After the titration is complete, raising the water bath temperature to 80° C. and maintaining the speed for continuous stirring for 1 hour. After the reaction is complete, filtering and cooling, obtaining an aqueous silicone-modified acrylate emulsion;

[0049] (6) Weigh 3 parts of nano-silicon oxide, 40 parts of deionized water, 20 parts of anhydrous ethanol, 3 parts of ammonia water, 3 parts of silane coupling agent KH-560, and 3 parts of tetraethyl orthosilicate in proportion, place them in a round-bottom flask and put them in a 50° C. water bath for stirring to make them stir evenly; then increase the temperature to 60° C. and add 1 part of saturated octadecylamine solution at one time, and continue stirring at 60° C. for 8 hours to obtain modified gel nano-silicon oxide;

[0050] (7) washing the modified nano-silica gel obtained in step (6) with anhydrous ethanol, centrifuging, drying at 80° C., and grinding to obtain hydrophobically modified nano-silica particles;

[0051] (8) Add 100 parts of silicone-modified acrylate emulsion into a container and stir, add 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 1.5 parts of hydrophobically modified silica nanoparticles, stir evenly, then add 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continue to disperse evenly, and let stand for 2 hours to obtain a water-based concrete composite anti-corrosion coating.

[0052] Example 3

[0053] (1) Weigh 0.58 parts of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate according to the proportion, add deionized water to dissolve, and stir at 25° C. and 800 r / min to make it completely dissolved to obtain an emulsifier solution with a solid content of 48.7%;

[0054] (2) Weigh 10 parts of methyl methacrylate, 12.2 parts of butyl acrylate, 1 part of acrylic acid, and 1 part of silicone monomer γ-methacryloxypropyltrimethoxysilane according to the proportion, stir evenly, take 10% of the total amount as seed monomer, and add dropwise to the emulsifier solution obtained in step (1), at 25° C., 800 r / min, and after sufficient pre-emulsification, obtain a milky white seed emulsion;

[0055] (3) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0056] (4) Weigh 0.2 parts of sodium bicarbonate into a four-necked round-necked flask, add the milky white seed emulsion obtained in step (2), place the flask in a water bath and add a stirring rod, add the milky white seed emulsion obtained in the previous step into the flask and start stirring at a speed of 350 r / min, set the water bath temperature to 72° C., place a condenser tube, and stir while heating; after the water temperature rises to 72° C., continue to keep warm and stir until the seed emulsion in the flask changes from white to blue;

[0057] (5) adjusting the water bath heating temperature to 75° C., continuing to heat and stir, adding the remaining monomer in step (2) and the ammonium persulfate solution obtained in step (3) into two constant pressure funnels respectively, and then dropping them into the flask. After the titration is complete, raising the water bath temperature to 80° C. and maintaining the speed for continuous stirring for 1 hour. After the reaction is complete, filtering and cooling, obtaining an aqueous silicone-modified acrylate emulsion;

[0058] (6) Weigh 3 parts of nano-silicon oxide, 40 parts of deionized water, 20 parts of anhydrous ethanol, 3 parts of ammonia water, 3 parts of silane coupling agent KH-560, and 3 parts of tetraethyl orthosilicate in proportion, place them in a round-bottom flask and put them in a 50° C. water bath for stirring to make them stir evenly; then increase the temperature to 60° C. and add 1 part of saturated octadecylamine solution at one time, and continue stirring at 60° C. for 8 hours to obtain modified gel nano-silicon oxide;

[0059] (7) washing the modified nano-silica gel obtained in step (5) with anhydrous ethanol, centrifuging, drying at 80° C., and grinding to obtain hydrophobically modified nano-silica particles;

[0060] (8) Add 100 parts of organosilicon-modified acrylate emulsion into a container and stir, add 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 3 parts of hydrophobically modified silica nanoparticles, stir evenly, then add 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continue to disperse evenly, and let stand for 2 hours to obtain a water-based concrete composite anti-corrosion coating.

[0061] Example 4

[0062] (1) Weigh 0.58 parts of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate according to the proportion, add deionized water to dissolve, and stir at 25° C. and 800 r / min to make it completely dissolved to obtain an emulsifier solution with a solid content of 48.7%;

[0063] (2) Weigh 15 parts of methyl methacrylate, 12.2 parts of butyl acrylate, 1 part of acrylic acid, and 1 part of an organic silicone monomer γ-methacryloxypropyltrimethoxysilane according to proportion, stir evenly, take 10% of the total amount as a seed monomer, and add it dropwise to the emulsifier solution obtained in step (1), at 25° C., 800 r / min, and after sufficient pre-emulsification, obtain a milky white seed emulsion;

[0064] (3) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0065] (4) Weigh 0.2 parts of sodium bicarbonate into a four-necked round-necked flask, add the milky white seed emulsion obtained in step (2), place the flask in a water bath and add a stirring rod, add the milky white seed emulsion obtained in the previous step into the flask and start stirring at a speed of 350 r / min, set the water bath temperature to 72° C., place a condenser tube, and stir while heating; after the water temperature rises to 72° C., continue to keep warm and stir until the seed emulsion in the flask changes from white to blue;

[0066] (5) adjusting the water bath heating temperature to 75° C., continuing to heat and stir, adding the remaining monomer in step (2) and the ammonium persulfate solution obtained in step (3) into two constant pressure funnels respectively, and then dropping them into the flask. After the titration is complete, raising the water bath temperature to 80° C. and maintaining the speed for continuous stirring for 1 hour. After the reaction is complete, filtering and cooling, obtaining an aqueous silicone-modified acrylate emulsion;

[0067] (6) Weigh 3 parts of nano-silicon oxide, 40 parts of deionized water, 20 parts of anhydrous ethanol, 3 parts of ammonia water, 3 parts of silane coupling agent KH-560, and 3 parts of tetraethyl orthosilicate in proportion, place them in a round-bottom flask and put them in a 50° C. water bath for stirring to make them stir evenly; then increase the temperature to 60° C. and add 1 part of saturated octadecylamine solution at one time, and continue stirring at 60° C. for 8 hours to obtain modified gel nano-silicon oxide;

[0068] (7) washing the modified nano-silica gel obtained in step (5) with anhydrous ethanol, centrifuging, drying at 80° C., and grinding to obtain hydrophobically modified nano-silica particles;

[0069] (8) Add 100 parts of silicone-modified acrylate emulsion into a container and stir, add 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 1.5 parts of hydrophobically modified silica nanoparticles, stir evenly, then add 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continue to disperse evenly, and let stand for 2 hours to obtain a water-based concrete composite anti-corrosion coating.

[0070] Example 5

[0071] (1) Weigh 0.58 parts of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate according to the proportion, add deionized water to dissolve, and stir at 25° C. and 800 r / min to make it completely dissolved to obtain an emulsifier solution with a solid content of 48.7%;

[0072] (2) Weigh 5 parts of methyl methacrylate, 12.2 parts of butyl acrylate, 1 part of acrylic acid, and 1 part of silicone monomer γ-methacryloxypropyltrimethoxysilane according to proportion, stir evenly, take 10% of the total amount as seed monomer, and add dropwise to the emulsifier solution obtained in step (1), at 25° C., 800 r / min, and after sufficient pre-emulsification, obtain a milky white seed emulsion;

[0073] (3) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0074] (4) Weigh 0.2 parts of sodium bicarbonate into a four-necked round-necked flask, add the milky white seed emulsion obtained in step (2), place the flask in a water bath and add a stirring rod, add the milky white seed emulsion obtained in the previous step into the flask and start stirring at a speed of 350 r / min, set the water bath temperature to 72° C., place a condenser tube, and stir while heating; after the water temperature rises to 72° C., continue to keep warm and stir until the seed emulsion in the flask changes from white to blue;

[0075] (5) adjusting the water bath heating temperature to 75° C., continuing to heat and stir, adding the remaining monomer in step (2) and the ammonium persulfate solution obtained in step (3) into two constant pressure funnels respectively, and then dropping them into the flask. After the titration is complete, raising the water bath temperature to 80° C. and maintaining the speed for continuous stirring for 1 hour. After the reaction is complete, filtering and cooling, obtaining an aqueous silicone-modified acrylate emulsion;

[0076] (6) Weigh 3 parts of nano-silicon oxide, 40 parts of deionized water, 20 parts of anhydrous ethanol, 3 parts of ammonia water, 3 parts of silane coupling agent KH-560, and 3 parts of tetraethyl orthosilicate in proportion, place them in a round-bottom flask and put them in a 50° C. water bath for stirring to make them stir evenly; then increase the temperature to 60° C. and add 1 part of saturated octadecylamine solution at one time, and continue stirring at 60° C. for 8 hours to obtain modified gel nano-silicon oxide;

[0077] (7) washing the modified nano-silica gel obtained in step (5) with anhydrous ethanol, centrifuging, drying at 80° C., and grinding to obtain hydrophobically modified nano-silica particles;

[0078] (8) Add 100 parts of silicone-modified acrylate emulsion into a container and stir, add 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 1.5 parts of hydrophobically modified silica nanoparticles, stir evenly, then add 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continue to disperse evenly, and let stand for 2 hours to obtain a water-based concrete composite anti-corrosion coating.

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 2 is that steps (6) and (7) are deleted, and step (8) is changed to adding 100 parts of organosilicon-modified acrylate emulsion into a container, stirring, adding 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 1.5 parts of unmodified silicon oxide nanoparticles, stirring evenly, and then adding 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continuing to disperse evenly, standing for 2 hours, and obtaining a water-based concrete composite anti-corrosion coating; the remaining steps are the same as those of Example 2.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 2 and Example 2 is that steps (6) and (7) are deleted, and step (8) is changed to adding 100 parts of silicone-modified acrylate emulsion into a container, stirring, adding 1 part of dispersant 5040 and 0.2 parts of wetting agent X-450, stirring evenly, adding 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continuing to disperse evenly, standing for 2 hours, and obtaining a water-based concrete composite anti-corrosion coating; the remaining steps are the same as those of Example 2.

[0083] Comparative Example 3

[0084] The difference between Comparative Example 3 and Example 2 is that steps (6) and (7) are deleted, and step (8) is changed to adding 100 parts of organosilicon-modified acrylate emulsion into a container, stirring, adding 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, adding 0.025 parts of evenly dispersed commercially available graphene oxide, stirring evenly, adding 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continuing to disperse evenly, standing for 2 hours, and obtaining a water-based concrete composite anti-corrosion coating; the remaining steps are the same as those in Example 2.

[0085] Comparative Example 4

[0086] The difference between Comparative Example 4 and Example 2 is that steps (6) and (7) are deleted, and step (8) is changed to adding 100 parts of organosilicon-modified acrylate emulsion into a container, stirring, adding 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, adding 1.5 parts of commercially available nano titanium dioxide particles, stirring evenly, adding 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2methyl-1-propanol, and 0.2 parts of benzoate in proportion, continuing to disperse evenly, standing for 2 hours, and obtaining a water-based concrete composite anti-corrosion coating; the remaining steps are the same as those of Example 2.

[0087] Comparative Example 5

[0088] The difference between Comparative Example 5 and Example 2 is that steps (6) and (7) are deleted, and step (8) is changed to adding 100 parts of organosilicon-modified acrylate emulsion into a container, stirring, adding 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, adding 1.5 parts of commercially available nano calcium carbonate particles, stirring evenly, adding 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2-methyl-1-propanol, and 0.2 parts of benzoate in proportion, continuing to disperse evenly, standing for 2 hours, and obtaining a water-based concrete composite anti-corrosion coating; the remaining steps are the same as those of Example 2.

[0089] Comparative Example 6

[0090] The difference between Comparative Example 6 and Example 2 is that steps (1) to (5) are changed to:

[0091] (1) Weigh 11 parts of methyl methacrylate, 1 part of methacrylic acid, 15 parts of butyl acrylate, and 3 parts of epoxy resin in proportion, stir at 25° C. and 800 r / min to obtain a monomer mixture;

[0092] (2) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0093] (2) Weigh 4 parts of octylphenol polyoxyethylene ether-10, 0.5 parts of sodium lauryl sulfate and 0.2 parts of sodium bicarbonate according to the proportion, mix them evenly, and place them in a round-bottom flask in a water bath at 55°C and stir for 30 minutes to make them evenly mixed. Control the dropping rate to drip 20% of the total number of the monomer mixed solution using a constant pressure dropping funnel within 30 minutes. After the dripping is completed, the temperature of the reaction system is raised to 70°C, and the ammonium persulfate solution obtained in step (2) and all the remaining monomer solutions are added. After all the materials are dripped, the temperature is continued to be raised to 80°C for insulation reaction for 1 hour, and the material is filtered out after cooling to room temperature to obtain epoxy acrylic emulsion; the remaining steps are the same as in Example 2.

[0094] Comparative Example 7

[0095] The difference between Comparative Example 7 and Example 2 is that steps (1) to (5) are changed to:

[0096] (1) Weigh 11 parts of methyl methacrylate, 1 part of methacrylic acid, and 15 parts of butyl acrylate in proportion, stir at 25° C. and 800 r / min to obtain a monomer mixture;

[0097] (2) weighing 0.15 parts of ammonium persulfate in proportion and completely dissolving it in deionized water 100 times its weight to obtain an ammonium persulfate solution;

[0098] (3) After 4 parts of octylphenol polyoxyethylene ether-10, 0.5 parts of sodium dodecyl sulfate, 40 parts of deionized water and 0.2 parts of sodium bicarbonate are mixed evenly, the mixture is placed in a round-bottom flask in a water bath at 55°C and stirred for 30 minutes to make the mixture evenly mixed. The dropping rate is controlled to drip 20% of the total monomer mixed solution using a constant pressure dropping funnel within 30 minutes. After the dripping is completed, the temperature of the reaction system is raised to 70°C, and the ammonium persulfate solution obtained in step (2), 4 parts of dodecafluoroheptyl methacrylate and all the remaining monomer solutions are added. After the dripping of all the materials is completed, the temperature is continued to be raised to 80°C for insulation reaction for 1 hour, and the material is filtered out after cooling to room temperature to obtain a fluorine-containing acrylic emulsion; the remaining steps are the same as those in Example 2.

[0099] Comparative Example 8

[0100] The difference between Comparative Example 8 and Example 2 is that steps (1) to (5) are deleted, and step (8) is changed to: 100 parts of commercially available silicone acrylic emulsion are added to the container, stirred, 1 part of dispersant 5040, 0.2 parts of wetting agent X-450, and 1.5 parts of hydrophobically modified silica nanoparticles are added, and after stirring evenly, 2 parts of alcohol ester 12, 1 part of sodium polyacrylate, 1 part of RM2020, 0.5 parts of 2-amino-2methyl-1-propanol, and 0.2 parts of benzoate are added in proportion, and the mixture is dispersed evenly and allowed to stand for 2 hours to obtain a water-based concrete composite anti-corrosion coating; the remaining steps are the same as those in Example 2.

[0101] Effect example

[0102] Table 1 below shows the performance analysis results of the waterborne concrete composite coatings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0103] Table 1

[0104]

[0105]

[0106]

[0107]

[0108] From the data comparison of the embodiment and the comparative example, it can be found that the present invention uses water-based organosilicon-modified acrylate emulsion as a film-forming substance. When it is coated on the concrete surface, there is an interaction force between the polymer chains on the surface of the emulsion particles, and the particles are close to fusion to form a film; functional groups such as carboxyl in the acrylate segment can undergo a cross-linking reaction under certain conditions, further improving the strength and density of the film, and the organosilicon segment will migrate to the surface of the film, making the coating hydrophobic. Due to the hydrophobic modification of the surface of the nano-silicon oxide particles, it has good compatibility with the organosilicon-modified acrylate polymer in the emulsion. During the drying and film-forming process of the coating, the nano-silicon oxide particles will fill in the pores of the polymer film, reducing the porosity of the coating and effectively preventing corrosive media; the organosilicon-modified acrylate polymer film and the nano-silicon oxide particles in the coating form a relatively dense protective layer, further improving the corrosion resistance of the coating. In addition, the nano-silicon oxide particles play a reinforcing role in the coating. When the coating is subjected to external force, the nano-silicon oxide particles can bear part of the stress and improve the hardness and wear resistance of the coating. At the same time, the cross-linked structure between the organosilicon-modified acrylate polymers also makes the coating have a certain toughness, which can resist external forces to a certain extent without breaking. This combination of rigidity and flexibility allows the coating to adapt to the deformation of the concrete structure during use, and will not easily crack or peel off. Furthermore, the functional groups in the acrylate polymer can chemically bond and physically adsorb with the concrete surface, improve the adhesion between the coating and the concrete matrix, and make the coating effectively play a protective role for a long time, avoiding the occurrence of peeling and loss of protective function. The coating prepared by the present invention uses an aqueous emulsion as a film-forming substance, reduces the emission of organic matter, has strong environmental protection, and is mixed with nanoparticles, and has excellent anti-corrosion performance.

[0109] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and no mark in the claims should be regarded as limiting the claims involved.

Claims

1. A method for preparing a water-based concrete composite anti-corrosion coating, characterized in that: The method comprises the following preparation steps: (1) providing an emulsifier solution; (2) weighing methyl methacrylate, butyl acrylate, acrylic acid, and silicone monomer γ-methacryloxypropyltrimethoxysilane in proportion, mixing them evenly, taking a portion of the mixture as a seed monomer, and adding it dropwise to the emulsifier solution obtained in step (1) to obtain a milky white seed emulsion; (3) weighing a pH buffer into a container, adding the white emulsion obtained in step (2) under heating conditions, and reacting until the solution changes from white to blue; (4) adding the remaining part of the mixture of step (2) and an initiator, heating, and obtaining an aqueous silicone-modified acrylate emulsion; (5) weighing nano-silica, deionized water, anhydrous ethanol, ammonia water, silane coupling agent KH-560, and tetraethyl orthosilicate in proportion in a container, heating and mixing, and then adding a hydrophobic long-chain modifier to react to obtain a modified nano-silica gel; (6) washing, drying, and grinding the modified nano-silica gel obtained in step (5) to obtain hydrophobic modified nano-silica particles; (7) Adding organosilicon-modified acrylic emulsion into a container, stirring, adding dispersant, wetting agent, hydrophobically modified silica nanoparticles, stirring evenly, adding film-forming aid, thickener, leveling agent, pH adjuster, mildew inhibitor according to proportion, continuing to disperse evenly, and obtaining a water-based concrete composite anticorrosive coating.

2. The method for preparing a water-based concrete composite anticorrosive coating according to claim 1, characterized in that: The emulsifier in step (1) is 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, and its mass ratio is 1-3% of the total mass of the four monomers in step (2).

3. The method for preparing a water-based concrete composite anticorrosive coating according to claim 1, characterized in that: In the step (2), the ratio of methyl methacrylate, butyl acrylate, acrylic acid and silicone monomer γ-methacryloxypropyltrimethoxysilane is 8-12:10.5-12.5:1:1; the ratio of the seed monomer is 5% to 15% of the total monomer mass.

4. The method for preparing a water-based concrete composite anticorrosive coating according to claim 1, characterized in that: The pH buffer in step (3) is sodium bicarbonate; the initiator in step (4) is ammonium persulfate, and its mass ratio is 0.3-1% of the total mass of the four monomers in step (2); and the hydrophobic long-chain modifier in step (5) is octadecylamine.

5. The method for preparing a water-based concrete composite anti-corrosion coating according to claim 1, characterized in that: The nano silicon oxide particles in step (5) have a particle size of 5 to 15 nm and a specific surface area of ​​180 to 220 m 2 / g.

6. The method for preparing a water-based concrete composite anticorrosive coating according to claim 1, characterized in that: The dispersant in step (7) is 5040; the leveling agent is RM2020; the thickener is one or more of sodium polyacrylate and polyurethane alkali swelling thickener; the wetting agent is one or two of CF-10, X-450 and TEGO Dispers 755W; the film-forming aid is alcohol ester twelve, and the defoaming agent is one or two of BYK306 and F-2-2; the mildew inhibitor is one or two of benzoate and benzyl carbamate chloride; the pH adjuster is 2-amino-2methyl-1-propanol pH adjuster.

7. A water-based concrete composite anti-corrosion coating, characterized in that: The water-based concrete composite anti-corrosion coating comprises, by components, 80 to 120 parts of water-based silicone-modified acrylate emulsion, 0.5 to 2.5 parts of hydrophobically modified nano-silicon oxide, 0.5 to 2 parts of dispersant, 0.1 to 1 part of leveling agent, 0.5 to 3 parts of thickener, 0.1 to 0.3 parts of wetting agent and defoamer respectively, 1 to 2 parts of film-forming aid, 0.1 to 0.4 parts of mildewproofing agent, and 0.3 to 0.5 parts of pH regulator; the anti-corrosion coating is prepared by the preparation method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Exterior wall coating and preparation method thereof

    CN101974273A

  • A nano-modified highly stain-resistant elastic coating and its preparation method

    CN102286233A

  • Inorganic nano particle modified composite waterproof emulsion and preparation method thereof

    CN102391410A

  • Waterborne silicone acrylate emulsion with core-shell structure and preparation method of waterborne silicone acrylate emulsion

    CN107226883A

  • Surface lipophilic modification method of nano-silicon dioxide and lipophilic nano-silicon dioxide prepared by method

    CN109370265A

Cited By

  • Cold galvanizing anticorrosive paint and preparation method thereof

    CN120966333A

  • Waterproof and decorative integrated coating and preparation method thereof

    CN121343481A